Cesàro Summable Sequence Spaces over the Non-Newtonian Complex Field - Uğur Kadak (Journal of Probability and Statistics)
The spaces ω0p, ωp, and ω∞p can be considered the sets of all sequences that are strongly summable to zero, strongly summable, and bounded, by the Cesàro method of order 1 with index p. Here we define the sets of sequences which are related to strong Cesàro summability over the non-Newtonian complex field by using two generator functions. Also we determine the β-duals of the new spaces and characterize matrix transformations on them into the sets of ⁎-bounded, ⁎-convergent, and ⁎-null sequences of non-Newtonian complex numbers.